Sapere aude: educação catalográfica crítica - Filipe Reis (2024)
Cataloging can be considered the intentional production of conditions for interaction between actors in a documentary context. These actors are commonly specified as documents and users. As a sub-discipline of Library Science, cataloging establishes theories, principles, models, methods, and instruments. Moreover, as a procedure, it develops representation of the descriptive and thematic aspects of documents. Librarians must be able to think critically about cataloging and its social impacts. Critical sense can be developed throughout the formation process of catalogers by using a set of actions that compose cataloging education. Among the relevant issues regarding cataloging education are the relationship between theory and practice, the syllabus, the competences of a cataloger, and the critical approach of cataloging. The aim of this research is to investigate the principles for a critical cataloging education that contribute to the rational, curious, creative, reflexive, analytical, and autonomous formation of students. Furthermore, the specific objectives include examining cataloging concepts to systematize the meanders of this sub-discipline in the educational process; addressing catalog education in the context of Library Science in order to identify and organize recurring issues; distinguishing and systematizing the concepts and theories that support a critical education to propose principles for a critical cataloging education. Hence, this research is classified as a basic research with a qualitative approach. Regarding its aims, it is exploratory and descriptive. As for the technical procedures, the research is primarily bibliographic. The development of the theme is structured as follows: section 1 is the introduction; in section 2 the methodological aspects of the research are defined; in section 3 - Cataloging, the topic is presented as a documentary process and, afterwards, there is an exposition and systematization of the concepts that support this process; in section 4 - Cataloging Education in Library Science, the field and its first courses are discussed; at last, in section 5 - Critical Cataloging Education, the principles of critical education and cataloging critical education are presented. As final considerations, it is concluded that Critical Cataloging Education is a pedagogical proposal for different cataloging courses that intend to conceive an ethical, curious, creative, and rational formation, and that aim to develop the intellectual emancipation of cataloging students.